Retrospective Assessment of the Success Rate of Single-Visit Root Canal Treatment: A Clinical and Radiographical Analysis - Ali M. Rashid (University of Mosul, College of Dentistry, 2008)
Aim: The purpose of this study was to determine retrospectively, clinically and radiographically the suc-cess rate of single-visit root canal treatment and determine the possible factors that could affected there prognosis.Materials and Methods: nine-hundred and sixty-five single-visi1 cases, of which 322 present for re-examination appointment ranging from 6 months to 5 years from the day of treatment were considered. Clinical and radiographical data were used to form overall impression of the outcomes for each case at the time of re-examination. Available demographics and treatment information of these 322 cases were compiled for comparison. The number of treatment visits was not determined by a pre-treatment diagnosis or a re-assessment of the pulp status upon entry in to the tooth; therefore both vital and necrotic cases, as well as those with and without periradicular pathosis, Were included. Statistical analysis was carried out using Chi-square test and considered variations in failure rates based on gender, tooth type, position and arch. A t-test was used to evaluate data on age. Results: The overall success rate was 92.8%. No statistically significan1 differences were seen based on gender and arches. The data show almost younger ages more candidate for failure rate than older age group. Statistically, anterior teeth were more successful than posterior teeth. Conclusion: The success rate of single-visit root canal therapy was engorgement for this approach .Both gender and arches were not affecting the treatment outcome in this study, where as the treatment for older age and anterior teeth more successful than younger and posterior teeth respectively.